Cooperative bundling by fascin generates actin structures with architectures that depend on filament length - Sherer, Laura A.; Courtemanche, Naomi (Frontiers in Cell and Developmental Biology, 2022)
The assembly of actin-based structures with precisely defined architectures supports essential cellular functions, including motility, intracellular transport, and division. The geometric arrangements of the filaments within actin structures are stabilized via the association of crosslinking proteins, which bind two filaments simultaneously. Because actin polymerization and crosslinking occur concurrently within the dynamic environment of the cell, these processes likely play interdependent roles in shaping the architectures of actin-based structures. To dissect the contribution of polymerization to the construction of higher-order actin structures, we investigated how filament elongation affects the formation of simple, polarized actin bundles by the crosslinking protein fascin. Using populations of actin filaments to represent distinct stages of elongation, we found that the rate of bundle assembly increases with filament length. Fascin assembles short filaments into discrete bundles, whereas bundles of long filaments merge with one another to form interconnected networks. Although filament elongation promotes bundle coalescence, many connections formed between elongating bundles are short-lived and are followed by filament breakage. Our data suggest that initiation of crosslinking early in elongation aligns growing filaments, creating a template for continued bundle assembly as elongation proceeds. This initial alignment promotes the assembly of bundles that are resistant to large changes in curvature that are required for coalescence into interconnected networks. As a result, bundles of short filaments remain straighter and more topologically discrete as elongation proceeds than bundles assembled from long filaments. Thus, uncoordinated filament elongation and crosslinking can alter the architecture of bundled actin networks, highlighting the importance of maintaining precise control over filament length during the assembly of specialized actin structures.